2019
DOI: 10.1016/j.neuroscience.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Ethanol Exposure Selectively Increases Synaptic Excitability in the Ventral Domain of the Rat Hippocampus

Abstract: Many studies have implicated hippocampal dysregulation in the pathophysiology of alcohol use disorder (AUD). However, over the past twenty years, a growing body of evidence has revealed distinct functional roles of the dorsal (dHC) and ventral (vHC) hippocampal subregions, with the dHC being primarily involved in spatial learning and memory and the vHC regulating anxiety-and depressive-like behaviors. Notably, to our knowledge, no rodent studies have examined the effects of chronic ethanol exposure on synaptic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 85 publications
2
37
1
Order By: Relevance
“…Chronic alcohol administration has also been associated with impaired performance in the other cognitive tasks such as the Hebb-Williams maze (working memory assessment; Bond and Digiusto, 1976;Fehr et al, 1976), the radial arm maze (spatial memory; Gál and Bárdos, 1994), the spontaneous alternation paradigm (spatial processing), the attentional set shifting (cognitive flexibility, dependent of frontal cortex; Vedder et al, 2015), the step-down passive avoidance task, the Greek cross maze, and the Shuttlebox task (Farr et al, 2005), all of them of which are related with avoidance learning, which involves the limbic system including the hippocampus (Gabriel, 1993). Chronic intermittent ethanol exposure (CIE) in vapor chambers increases the anxiety-like behaviors in the adult male rats, possibly related to the alterations in the synaptic activity of the ventral hippocampus and not of the dorsal hippocampus (Ewin et al, 2019).…”
Section: Alcohol Consumption In Adult Rodentsmentioning
confidence: 99%
“…Chronic alcohol administration has also been associated with impaired performance in the other cognitive tasks such as the Hebb-Williams maze (working memory assessment; Bond and Digiusto, 1976;Fehr et al, 1976), the radial arm maze (spatial memory; Gál and Bárdos, 1994), the spontaneous alternation paradigm (spatial processing), the attentional set shifting (cognitive flexibility, dependent of frontal cortex; Vedder et al, 2015), the step-down passive avoidance task, the Greek cross maze, and the Shuttlebox task (Farr et al, 2005), all of them of which are related with avoidance learning, which involves the limbic system including the hippocampus (Gabriel, 1993). Chronic intermittent ethanol exposure (CIE) in vapor chambers increases the anxiety-like behaviors in the adult male rats, possibly related to the alterations in the synaptic activity of the ventral hippocampus and not of the dorsal hippocampus (Ewin et al, 2019).…”
Section: Alcohol Consumption In Adult Rodentsmentioning
confidence: 99%
“…Both clinical and preclinical studies have shown that increased BLA excitability is a common feature of AUD and comorbid diseases, like generalized anxiety disorder and post-traumatic stress disorder [4,48,49]. Interestingly, BLA projections to the hippocampus are largely restricted to the ventral domain of this brain region and we have recently reported that a model of vulnerability to AUD and a model of alcohol dependence both lead to increases in hippocampal synaptic excitability that are exclusively restricted to the ventral region of the hippocampus [14,50]. Although additional studies will be needed to establish a causal role of BLA-vHC dysregulation in the behavioral phenotypes promoted by these models, these emerging findings are consistent with the idea that maladaptive increases in BLA-vHC synaptic communication may contribute to both the anxiogenic behaviors and excessive alcohol drinking associated with AUD and comorbid affective conditions.…”
Section: Discussionmentioning
confidence: 89%
“…While human imaging studies do not differentiate dorsal and ventral areas of the hippocampus, preclinical work in the 1980's suggests that the ventral portion of the hippocampus may be more susceptible to ethanol-related plasticity, exhibiting larger reductions in spine density (Lescaudron & Verna 1985). Interestingly, more recent work supports the idea that the vHC may be more vulnerable to ethanol exposure with reports demonstrating increased excitability which was associated with reduced expression of key proteins that regulate synaptic transmission in the vHC (Almonte et al 2017;Ewin et al 2019). Although this appears opposite to the data presented here, given the complex interactions between the hippocampal subregions in the ventral hippocampus (CA1, CA2, CA3 and Subiculum), sorting out the multifaceted effects of ethanol on neuronal function in this area and ultimately determining how these alterations influence behavior will be an important undertaking.…”
Section: Discussionmentioning
confidence: 99%
“…The work presented here reveals a complexity in hippocampal function with regards to ethanol drinking behavior that requires further study to understand. Much of the work supporting a role for the hippocampus in various behaviors relies on permanent or reversible lesions, however more recent work using newer, more selective technology is emerging that is helping to resolve unanswered questions and, at the same time, reveal the complex function of this heterogenous structure (Barker et al 2019;Britt et al 2012;Ewin et al 2019;Scudder et al 2018;Yu et al 2017). Despite the exciting directions that research in this area is going, many questions regarding ventral hippocampal functional remain unresolved.…”
Section: Discussionmentioning
confidence: 99%